(untitled) (American Journal of Islam and Society, 2018)
Edward E. Curtis IV is one of the most important scholars of Islam in the United States. This slim volume is a welcome addition to his work, and should be required reading for all who are interested in the place of Muslims within the history of America. One also wishes that the book be read widely by American Muslims. As the latter day prophet, Bob Marley, once sang about other soldiers in the Americas, “If you know your history/ Then you would know where you’re coming from.” Curtis’ book helps us, as American Muslims, to learn about our own history in our country. The book is not written for a specialized audience, and could easily be used by undergraduate or even senior high school students in a number of courses on Islam or religion in America. It is a very short volume, coming in at 82 pages of text with a single additional page of notes. The book is divided into five chapters of roughly equal length. The first chapter introduces the contemporary issues of American Muslim soldiers in the United States armed forces through the stories of Captain Humayun Khan and Corporal Kareem Rashad Sultan Khan. Corporal Khan became widely known when a photo of his mother, Elsheba, cradling his gravestone was mentioned by General Colin Powell in the 2008 election. Captain Khan’s introduction to the American public was more recent, when his father, Khizr, spoke about his son’s sacrifice on the final night of the Democratic National Convention in 2016 ...